(NsOWREMENNYE MUZYKALXNO(B-(NKOMP@TERNYE TEHNOLOGIIs (NMETODIKA(B.(Nu^EBNOE POSOBIEs - (Na(B.(Nw(B.(NaNDERSENs ((NsANKT(B-(NpETERBURGs (NlANXs (NpLANETA MUZYKIs, 2021)
(NpREDLAGAEMOE U^EBNOE POSOBIE OBRAZOWATELXNOGO MODULQ WKL@^AET DISCIPLINY PROFILXNOJ PODGOTOWKI PO MUZYKALXNO(B-(NKOMPX@TERNYM TEHNOLOGIQM(B.s
Keywords: (NmETODIKAs